Inductores de floracion en mango (mangifera indic L.) variedad tommy en el cantón colimes - Ortiz Chipre, Martin De Jesus (2012)
This research was conducted at the Hacienda "Pivano" located in the Campus The Reliquary Km 80 via Guayaquil - Balzar, Colimes canton, Guayas Province. Whose location is 1 ° 33 '43 "South latitude and 79 ° 56' 45" west longitude at a height of 30 meters. The experiment lasted 180 days. In this paper we used a 3 x 3 factorial arrangement +1 a witness willing Design Randomized Complete Block (RCBD) with 3 replications. For the functional test was applied Tukey's multiple range (P <0.05 and P = 0.01). There was the three-inducing effect on early flowering in mango, since all were ahead in six days average flowering. The treatment produced the greatest number of inflorescences was potassium nitrate with 50 g who obtained the highest number of inflorescences with 6.28. The total yield in kg / tree knew with potassium nitrate treatment dose with 119.50 30gramos kg.Al perform economic analysis of the study treatments The best cost / benefit ratio for treatment was recorded in T2 (KNO3 3%) with 1, $ 77, and the benefit - cost ratio was less efficient for the treatment T5 (NH4 NO3 3%) with 1.29. The best performance was given with treatment T2 (KNO3 3%) with 77.13%, followed by treatment T10 (control without inductor) with 64.07%.